(untitled) (Bangladesh Journal of Zoology, 2012)
Biodiversity studies in search of endoparasitic acephaline gregarines of the earthworms of Dhaka, Bangladesh, revealed a new species under the genus Nematocystis Hesse, 1909. The species was obtained from the seminal vesicles of the earthworm Metaphire peguana Rasa, 1890. It is a perfectly ribbon like organism, solitary, cylindrical, with several bulges and foldings in the middle portion of the body, especially in mature forms. Mature gamont measures 1955.85-1989.0 (1970.215 ± 13.830) ?m in length and 48.62-53.04 (51.714 ± 2.135) ?m in width. Nucleus small and rounded, measures 26.52-33.15 (29.835 ± 2.992) ?m in length and 17.68-22.01 (19.448 ± 2.282) ?m in width. Gametocysts spherical with two approximately equal sized gametocytes. It measures 110.05- 121.55 (116.24 ± 4.908) ?m in length and 88.04-99.45 (93.925 ± 5.823) ?m in width. Oocysts biconical, measuring 22.1-30.94 (26.962 ± 3.870) ?m × 11.05- 15.47 (13.26 ± 2.08) ?m. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12894 Bangladesh J. Zool. 40(1): 51-58, 2012